Literature Review: Potential of Coriander (Coriandrum sativum L.) as a Source of Natural Antioxidants - Mutiara Ghina; Elsa Yuniarti; Yusni Atifah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Indonesia is a country known for its richness in spices, one of the spices that is widely used by the people of Indonesia is coriander. Coriander is a spice that has many antioxidant compounds and biological activities that have the potential to be utilized as a source of natural antioxidants. The purpose of writing this article is to find out the potential of coriander plants as a source of natural antioxidants through literature review. The method used in writing this article is a Literature Review Article (LRA) with the Preferred Reposting Items for Systematic Review and Meta-Analysis (PRISMA) approach. Based on the results of the reviewed articles, 11 relevant articles were obtained stating that coriander has the potential as a source of natural antioxidants. coriander extract and its antioxidant compounds have biological activities such as antiinflammatory, antidiabetic, anticholesterol, and anticancer, so they can be used as herbs in the treatment of disease.